Estudo da variação do número de tubos em trocador de calor casco e tubos em CFD - Souza, Caio Luiz Rodrigues de (2019)
The thermal analysis is of essential importance in the design of the heat exchanger. In shell and tube heat exchangers of industrial dimensions, it is interesting to computational fluid dynamics analysis CFD (Computational Fluid Dynamics), because it is fast to obtain reliable and cost-effective results, if correctly designed, in relation to experimental methods as pilot plant. Actually, the computational numerical study doesn’t replace the experimental methods, but in a joint work it is possible to obtain accurate results, reducing the project study time. The present work intends to analyze and compare the influence caused on a steady state shell and tube heat exchanger by varying the number of tubes through Ansys CFX, a CFD. The interest is the validation of the computational method, analyzing the exchanger outlet temperature and the pressure drop generated by changing the number and arrangement of tubes in the heat exchanger. After analyzing the raphs, it can be concluded that the simulations presented satisfactory results even with the limitations.